Pharmacological Influences on the Neolithic Transition. Issue Volume 35:Issues 3(2015) (October 2015) - Wadley, Greg; Hayden, Brian
While uncertainty remains as to the relative importance of the factors that propelled Neolithization at different sites, a model is gaining traction that proposes that cereal cultivation was adopted in part to produce alcohol for competitive feasting. The model ties together the emergence of two key phenomena – cereal cultivation and social inequality – and is supported by a variety of archaeological and ethnographic data. However pharmacological theory has not yet been explicitly deployed in the presentation of the model; rather its development has relied on a common-sense understanding of the effects of alcohol and its cross-cultural importance in social life. Our aim in this paper is to bring understandings of drug use from pharmacology and related disciplines to bear upon the challenge of explaining Neolithization. We find that pharmacological theory sheds light on the importance of alcohol and other mood-altering products of Neolithic farming. In particular there is support for some influence of pharmacoactivity on Neolithic social evolution, which might extend beyond a role in feasting to include modulation of responses to status hierarchies, increased residential densities, and more intense work schedules. We propose that pharmacological influences be incorporated into models of the Neolithic transition.